Interpreting repetition expressions in the writing of Trump’s addresses during the Covid-19 pandemic - Mister Gidion Maru; Gin Gin Gustine; Slamet Setiawan; Julio Juniver Tadete; Tirza Kumajas (Universitas Pendidikan Indonesia, 2023)
The emergence of the Covid-19 pandemic has driven a world crisis that requires world leaders to respond by voicing their policies and solutions. The political addresses serve to be the path for these purposes. This creates the need for effective rhetorical strategies or forms used by leaders, particularly presidents, to address the current issues which are not commonly beheld. This study shares the result of the inquiry on the use of repetition in President Donald Trump’s speeches during the Covid-19 Pandemic in America. The study attempts to interpret the type of repetition found in the speeches and their general meaning implications. As a textual study, this research gained data from three speeches of Trump specifically addressing the issue of the Covid-19 pandemic delivered during his attempt to handle the emergence and spread of the Coronavirus in the U.S. since in American literature, an address is also viewed as a literary work, this study deployed Goffman’s frame analysis which is also regarded as double hermeneutic for the analysis process. The findings, then, designate that Trump, in his addresses, applied seven types of repetition; from anaphora to root repetition. Further, the study found that anaphora serves to be the most used repetition, which means the main rhetorical instrument in the addresses. In terms of meaning implications, the repetitions apparently imply the reawakening of the jeremiad structure in the address and the affirmation of the American sense of greatness and role in the world. The findings of this inquiry are hoped to add more theoretical constructions and strategies for rhetoric texts for both crisis and socio-political communication contexts. Its practical contribution goes toward defining and exemplifying language expressions and functions in communicative text writing.